2020
DOI: 10.1109/access.2020.3016041
|View full text |Cite
|
Sign up to set email alerts
|

A Privacy-Preserving Framework With Self-Governance and Permission Delegation in Online Social Networks

Abstract: With the wide use of online social networks (OSNs), the problem of data privacy has attracted a lot of attention from not only the research community but also the general public. To meet the privacy needs of OSNs, we present a new framework for protecting information published through online social network websites through encryption by taking into account special features of OSNs. In this framework, autonomous private communities, called as zones, are set up by one or a set of mutually-trusted users collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Additionally, to protect the privacy of this sensitive information, unique software tools and cryptographic security protocols must be employed using the user's settings [16,26]. Hardware devices must be put inside the linked system to improve these security settings.…”
Section: Countermeasuresmentioning
confidence: 99%
“…Additionally, to protect the privacy of this sensitive information, unique software tools and cryptographic security protocols must be employed using the user's settings [16,26]. Hardware devices must be put inside the linked system to improve these security settings.…”
Section: Countermeasuresmentioning
confidence: 99%
“…Koltay's study allows us to note the proximity of data governance to information and technology governance [46]. Guo et al discuss privacy in the context of self-governance and social networks [47]. From the perspective of ISO/IEC 27002:2013, Solana-González et al found that practices related to privacy and protection of personal identifiable information play the least role in the decision-making process related to improvements in information security requirements in organizations [48].…”
Section: Further Workmentioning
confidence: 99%